2016
DOI: 10.7196/samj.2016.v106i4.8777
|View full text |Cite
|
Sign up to set email alerts
|

Use of the nested polymerase chain reaction for detection of Toxoplasma gondii in slaughterhouse workers in Thika District, Kenya

Abstract: Background. The widely used methods of diagnosis of Toxoplasma gondii are serological. Current reports indicate a high seroprevalence of T. gondii in humans in Kenya. There is a need for more sensitive diagnostic tests, especially when the specific antibody titres are below detectable threshold levels. Use of the polymerase chain reaction (PCR) targeting the repetitive 529 base pair loci has been reported to be sensitive and specific. Objective. To detect T. gondii in a high-risk group of public health workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The study was undertaken in an area which was previously shown to have high prevalence of T. gondii among the slaughterhouse workers [9]. The high (79%) prevalence of T. gondii in all the areas showed that the free-range chickens are a major reservoir for T. gondii parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was undertaken in an area which was previously shown to have high prevalence of T. gondii among the slaughterhouse workers [9]. The high (79%) prevalence of T. gondii in all the areas showed that the free-range chickens are a major reservoir for T. gondii parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, detection of T. gondii DNA in brain samples was done by nPCR, based on the multilocus 529 bp repeat element which gives increased diagnostic sensitivity and accuracy compared to that which can be obtained when targeting the B1 gene that exists in 35 copies/genome [13, 28]. However, the sensitivity of PCR may be limited by the random distribution of the parasite and varying parasite densities in affected tissue [9, 29]. The use of PCR may also be limited by the need for thermocycler, expensive reagents, and skilled manpower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D3025) and amplification of the 529 bp repeat units was carried out by nested PCR as previously described [14, 15]. Secondary amplification products were electrophoresed on 1.5% agarose gel stained with ethidium bromide and visualized under ultraviolet (UV) light.…”
Section: Methodsmentioning
confidence: 99%
“…In another study carried out by Njuguna et al [ 49 ] to establish the prevalence of gastrointestinal (GIT) parasites in fecal samples of 103 cats kept by households in Thika region, Toxoplasma gondii was detected in 7.8% (95% CI: 4.5–11.1%) of the samples collected. Another recent study in Thika region showed that up to 39% of the slaughterhouse workers were infected with T. gondii as detected using nPCR [ 50 ].…”
Section: Introductionmentioning
confidence: 99%